Two new species and new records of Neotropical Culicoides Latreille (Diptera: Ceratopogonidae) - Spinelli, Gustavo R.; Ronderos, Maria M.; Díaz, Florentina (Zootaxa, 2021)
The following two new species of biting midges of Culicoides Latreille are described and photographed: Culicoides carbonelli Spinelli & Martínez from Uruguay, and C. dellapei Spinelli, Ronderos & Díaz from Argentina. Culicoides crucifer Clastrier, 1968 and C. hoffmani Fox, 1946 are diagnosed and newly recorded from Argentina, and the studied specimens are photographed.